INVESTIGATING VIRTUAL INSTRUCTOR ROLES AND ONLINE TEACHING EXPERIENCE: A PROGRAM LEVEL CASE STUDY - Achwarin, Naree; Brahmakasikara, Laura M; Cleesuntorn, Athipat (Journal of Interdisciplinary Research (ISSN: 2408-1906), 2017)
Delivery of distance education via internet-based technology to make learning interactive and collaborative has become increasingly accepted in education nationwide and worldwide. New technologies provide opportunity and challenge teachers to perform virtual instructor roles. This research study reflected on the virtual instructor roles and online teaching experiences towards eLearning delivery mode. The objective of the study was to explore the virtual instructor roles and online teaching experiences at the program level at the Graduate School of eLearning, Assumption University of Thailand. The virtual instructor roles included three dimensions: pedagogical dimension, managerial dimension, and technological dimension. A qualitative case study method was used in this study which included the instructors’ positive impression towards online teaching experiences. The respondents for the study were 15 faculties members from five online graduate programs at the Graduate School of eLearning, Assumption University of Thailand. The structured questionnaire was used to obtain qualitative data. The content analysis was used to analyze qualitative data. Findings revealed that there were some similarities and differences in reflections, impressions, and online teaching experiences among the faculty members.